REPLICATION OF CHARACTER CLOTHING ADAPTED FROM THE CHARACTER LEAFA IN THE SWORD ART ONLINE SERIES - Daiva Naflah Nurizka; Cucu Ruhidawati (Journal of Social Research, 2024)
Every clothing must have utility, beauty, or distinctiveness to keep buyers interested. Creative clothing is one type of apparel that is both unique and very creative. Creative clothing is clothing created as a consequence of a person's imagination, wishful thinking, thoughts, ideas, or inspiration to express creativity. The inspiration or inspirations for designing these imaginative garments might vary, such as the fantasy-themed animation series Sword Art Online. Sword Art Online is a fantasy series that prompted researchers to create imaginative attire, with the series' character Leafa serving as the primary inspiration. Leafa is a character from Suguha's sylph race in the Alfheim Online game who assists her older brother, Kirito, in saving Asuna, who is trapped in the game. This study intends to foster the writer's creativity by creating unique apparel and utilizing what he or she has learned in class. This study used the PPE model technique, which has three stages: planning, production, and assessment. This study creates unique attire that complements Leafa's qualities by using glossy textiles that provide a stunning and glamorous visual impression. The wing embellishments on this unique clothes add to its appeal and consistency with the theme.